Commercial law in Malaysia - Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (Prentice Hall, 2008)
This book has its origin in a compilation of lecture notes of the Commercial Law and Malaysian Business Law which are the core courses for Bachelor of Accounting and Bachelor of Business Administration students of the International Islamic University Malaysia. Its primary objective is to provide students commencing legal studies and also lay readers a general overview on the commercial legal environment in Malaysia. In particular, this book is designed to meet these specific objectives: • To equip the readers with a basic understanding of the commercial laws in Malaysia • To expose to the readers on haw to refer and apply the laws when they are involved in the commercial transactions • To study the Shari'ah principles regulating commercial transactions and compare to that of conventional dealings